Penerapan Metode Diskusi Kelompok Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Dalam Pembelajaran IPS - Cipto Duwi Priyono (Journal Education Innovation (JEI), 2024)
One of the causes of the low ability of critical thinking students is the lack of engagement, lazy invited thinking, and activity of the students during the learning process progresses, the learning process is carried out based on the teacher, and the students learn thinking ability is acquired. One of the ways that can be used to enhance the critical thinking ability of students is by applying the method of discussion. This research was conducted to know the ability of critical thinking in students of class V in MI Al-Hasanah Lumban Dolok Sub Siabu village of Mandailing Natal. The research uses descriptive qualitative research techniques with class action (PTK) adapted from Kemmis and Taggart models—data collection tools for observation ability and critical thinking. The research results showed that the critical thinking ability of students has increased after learning through the application of the method of discussion. It can be seen from the percentage of critical thinking ability that has increased every cycle. The results score the total critical thinking ability of students who accessed cycle I was 53 percent of the total score, 57% in cycle II 63 a percentage of 70%, and a total score on cycle III 72 with a rate of 80%. It can be inferred that. The discussion method influences the enhancement of critical thinking ability in students of class V in MI Al-Hasanah Lumban Dolok Sub Siabu village of Mandailing Natal